GOVERNMENT POLICY DIRECTIONS IN DEVELOPMENT START UP OF THE ECO DIGITAL MOTION SUPPORT PIONEERS INNOVATIVE PRODUCTS IN NEW NORMAL ERA - Putri Robiatul Adawiyah (POLITICO, 2021)
The purpose of this study was to determine the strategy and direction of government policies in the development of start-up startups supporting the new normal era of innovative eco-digital products. Through this research, it will be studied how the direction of Government policy in developing startup startups in Indonesia, as well as what government support is in keeping the eco-digital movement of innovative products stable in the new normal era, and what kind of startups can survive during a pandemic and new normal. This research method uses qualitative descriptive and literature studies based on primary data and secondary data from the results of data analysis from pilot business groups, groups of start-up policy makers, community policy users and startup business consumers. The results of the research show that the policy directions that must be the attention of the Indonesian government regarding the development of startups in Indonesia are as follows: Increasing Broadband access; Helping SMEs to switch to the online realm; Expanding the electronic payment system; Expanding access to finance (investment); Extending e-government services; socializing the Job Creation Law, which was recently passed to provide various impacts on the startup business ecosystem; The Creative Economy Agency (Bekraf), currently the government through the Indonesian Creative Economy Agency (Bekraf) is trying to build infrastructure to support the presence of startups in Indonesia. BEKuP (Bekraf for pre startup); In collaboration with MIKTI (IT Creative Industry Society) and Telkom Bekraf will hold intensive workshops for people who intend to build startups in 15 big cities; Making the University as a Startup Startup Incubator; Protecting MSME products from Curent Account Deficits (CAD) problems; Disseminating Government Regulation (PP) Number 74 of 2017; Prepare an electronic-based national trade road map (E-Commerce Road Map), hereinafter referred to as the 2017-2019 SPNBE Road Map; Funding programs, taxation, consumer protection, education and human resources (HR). Also communication infrastructure, logistics, cybersecurity, and the establishment of the SPNBE Roadmap implementing management; The government cuts the final PPh by 0.5% for MSMEs. Also through PMK Number 150, 2018, this digital industry can get income reduction incentives (PPh) or tax holidays; Facilitating creative ideas, innovations, originality ideas, and not end users through Grant activities and competitions in various aspects of local creative endeavors, academic research and technology; Provide liquidity, guarantee LPS Deposit insurance agency to owners of capital; Prepare financing in the technology sector. Prepare a law on the national knowledge and technology system; Evaluating educational curricula with graduate expertise, especially in tertiary and senior secondary education as well as developing research at universities.